Răspuns :
[tex] \sqrt{2}( \sqrt{2} + \sqrt{3}) - \sqrt{3}(2 \sqrt{3} + \sqrt{3}) = \\ \\ \sqrt{2}( \sqrt{2} + \sqrt{3}) - \sqrt{3} \times 3 \sqrt{3} = \\ \\ \sqrt{2}( \sqrt{2} + \sqrt{3}) - 3 \sqrt{3 \times 3} = \\ \\ \sqrt{2}( \sqrt{2} + \sqrt{3}) - 3 \sqrt{9} = \\ \\ \sqrt{2}( \sqrt{2} + \sqrt{3}) - 3 \times 3 = \\ \\ \sqrt{2}( \sqrt{2} + \sqrt{3}) - 9 = \\ \\ 2 + \sqrt{6} - 9 = \\ \\ - 7 + \sqrt{6} [/tex]
√2*(√2+√3)-√3*(2√3+√3)=
=2+√6-√3*3√3=
=2+√6-3*3=
=2+√6-9=
=-7+√6
Sper că ţi-am fost de folos!